Performance Analysis of Women in Central Bank Monetary System using Business Intelligence (Global Journal of Management and Business Research, 2019)
Gender diversity is a great concern in the globe. Women's have multidimensional skills and they are able to execute multiple tasks concurrently. But the representation of women's are very less as per literatures available in the globe. In the same line Central bank women's participation is not known completely and many questions are unanswered yet. In this paper we are trying to get the solution of the problem.
Keywords: gender parity; central banking; business intelligence; women#x2019; s participation in federal body